Coastal vulnerability modelling and social vulnerability assessment under anthropogenic impacts - Lu, Jingfang; Zhang, Yibo; Shi, Honghua; Lv, Xianqing (Frontiers in Marine Science, 2022)
Coastal regions are highly vulnerable to the impacts of human activities, land cover change, sea level rise (SLR), and climate extremes. In this study, we attempt to address this issue by simulating the spatial interactions among natural hazards, ever-increasing human activities, and social vulnerability in the south coast of the Bohai Sea, China. It is found that the activities occurring on land, especially within coastal environments, such as agricultural pond and ports, and those in the ocean (tide and residual current) both impose disaster risks on the marine environment. In 2020, 25.2% of the total study area is highly vulnerable, which is 21% larger than that in 1997. The socially vulnerable areas are mainly distributed in the southeast coast of the Laizhou Bay. These areas should be strengthened to reduce and prevent the storm surge and flood disasters. Ultimately, we emphasize the urgent needs to implement effective policy measures for reducing tomorrow’s risks from natural hazards.